Meta-analysis of methodological artifacts of the phylogenetic imbalance. - Smrčková, Jana (Jihočeská univerzita, 2011)
The influence of possible methodological artifacts (e.g. type of data or tree construction methods) on the tree topology was evaluated. A total of 413 phylogenetic trees was downloaded from the tree repository TreeBASE. Three indices of topology imbalance were employed, namely, Fusco & Cronk index, weighted average, and Colless index. The study reveals that methodological artifacts have probably a weak influence on the tree shape. Therefore, patterns in tree balance could reflect macroevolutionary processess, not a methodological bias.
Meta-analysis of methodological artifacts of the phylogenetic imbalance.
Keywords: fylogeneze; tvar stromu; nevyváženost; topologie; meta-analýza; phylogeny; tree shape; imbalance; topology; meta-analysis